Ritual do ator em grupo: o conceito de treinamento a partir da trajetória do Grupo Sonhus Teatro Ritual - Rocha, Fernando Alves (2014)
The objective of this work is the study of concepts and approaches present in an artistic process of building and maintaining a theater group, specifically that concern their creative processes and training or maintenance and development of their language and the art of its actors. Therefore, this work joined the organization and analysis of creative procedures, tests and actor training, from the artistic experience of the inserted researcher in the study object, the Sonhus Group Ritual Theatre. The study relies on approaches that integrate both the participant observation ethnological and phenomenological description, applied within a qualitative research methodology. The result of participant observation was later linked to other bibliographic references and experience reports from other actors participants active in the Group\'s history through semi-structured interviews prepared by the researcher, reflective training and surveys of some experiments, techniques and procedures performed in collective over eighteen group. The issue of research rests on two lines of force and motivating questions: what parameters indicate qualitative differences that define the uniqueness of a theater group in the organization and how the body technical preparation qualitatively interfere in artistic language of ritual significance of work.